Genetic, antimicrobial resistance profile and mortality rates of Acinetobacter baumannii infection in Brazil: A systematic review - Silva, Mirian CB.; Werlang, Maria HB.; Vandresen , Deborah F.; Fortes, Paulo CN.; Pascotto, Claudisséia R.; Lúcio, Léia C.; Ferreto, Lirane ED. (Narra Sains Indonesia, 2022)
The increase of multidrug-resistant bacteria - including Acinetobacter baumannii (A. baumannii) - has been reported globally. The aim of this systematic review was to determine the risk factors of A. baumannii infection, its resistance profile, reservoirs and mortality rates in Brazil. Data from over 3,000 patients were included. Results suggested that A. baumannii is widely transmitted in Brazil and the endemic clones ST1, ST15, ST 25, ST79, ST162 and ST730 were the most reported; also, blaOXA23, blaOXA51 and blaOXA143 were common resistant genes. The risk factors for A. baumannii infectionincluded the procedure of using invasive devices, previous antibiotic therapy, hemodialysis, comorbidities and higher scores on the Sequential Organ Failure Assessment (SOFA). Two out of five studies identified multidrug resistant A. baumannii to polymyxin. Mortality rates varied between 43.7% to 81%, except for the ST25 strain in which there was a 100% mortality rate. Mortality was associated with sepsis, respiratory infection, septic shock, old age (>60 years) and administration of norepinephrine. Nonetheless, this review highlights the need for more data on A. baumannii infectionacross Brazil to support public policies aiming to control and prevent the dissemination of this bacteria.